A Multidisciplinary Approach to the Study of Adamantyl Aminoguanidines – A New Class of Potentially Bioactive Compounds - Šekutor, Marina (Synlett, 2015)
Although adamantyl aminoguanidines have great potential as pharmacophores, their preparation and characterization has only recently been described. A detailed study of this class of compounds is presented here, with special emphasis on their physico-chemical properties as well as the evaluation of their biological application.
Keywords: adamantane; aminoguanidine; liposomes; enzyme inhibition; anion receptors